Examining the impact of chronic diseases on activities of daily living of middle-aged and older adults aged 45 years and above in China: a nationally representative cohort study - Ai, Zhonghua; Tang, Churou; Wen, Xuan; Kartheepan, Karthikesu; Tang, Songyuan (Frontiers in Public Health, 2024)
China has by far one of the fastest-aging populations in the world. Increasing age is often accompanied by an increasing prevalence of chronic diseases and impaired Activities of Daily Living (ADL). The aim of this study was to analyze the effects of chronic diseases on ADL in Chinese middle-aged and elderly people and to provide a scientific basis for delaying the impairment of ADL and prolonging the self-care life expectancy of middle-aged and older adults.This investigation utilized the survey information of 10,096 middle-aged and elderly people from the China Health and Aging Tracking Survey (CHARLS) of 2011 as baseline data, then followed up this cohort until 2018, and performed multifactorial analyses using Cox proportional risk models to explore the strength of the associations between chronic diseases and the risk of impaired ADL in middle-aged and older adults.RESULTS: Among the middle-aged and elderly population, the presence of hypertension was associated with a 38% higher risk of impaired ADL compared to those without the condition (HR=1.38,95% CI:1.24-1.54); the involvement of heart disease was associated with a 27% higher risk of impaired ADL compared to those without the condition (HR=1.27,95% CI:1.10-1.46); the existence of arthritis was associated with a 38% higher risk of impaired ADL in middle-aged and older adults compared to those without arthritis (HR=1.38,95% CI:1.25-2.08); additionally, the risk of impaired ADL with one or ≥ 2 chronic diseases was increased by 34% (HR=1.34, 95%